L’autocentrage ou l’évolution dans la structure énonciative du discours politique - Jereczek-Lipińska, Joanna (Wydawnictwo Naukowe UAM, 2012)
This study is based upon discursive and logometric analysis of the political speeches delivered by the candidates during the campaign and pre-campaign phases of the 2012 presidential elections in France, taking into account the results of previous studies related to the 2007 presidential elections. The present paper aims at tracing the different representations of the speaker within his own speeches and at analyzing the way he verbalizes himself in his campaign by observing the use, the distribution, the role and the possible impact of “I” and of the other personal pronouns within the frame of political communication. The analysis of statistical data tends to emphasize syntactic as well as morphological, stylistic, lexical, and gramatical distinctive features of the speeches delivered by the candidates to the presidential elections, especially in relation with the new possibilities conveyed by internet.
Evolution in the enunciative structure of the political discourse
Keywords: discourse analysis; political speech; personal pronoun; enunciative structure